FINANCIAL EDUCATION AND ITS IMPACT ON THE MANAGEMENT OF THE PERSONAL FINANCES OF THE IAFAS ADMINISTRATIVE AUDITOR - Risco Aquino, Karina (2025)
The research analyzes the relationship between financial education and personal finance management of the administrative auditor of the Health Insurance Fund Administrative Institutions (IAFAS), therefore, its general objective was to determine that financial education affects the management of the personal finances of the administrative auditor of the IAFAS of Central Lima December 2024. Regarding the methodology, the research adopted a quantitative approach, cross-sectional non-experimental design of correlational scope, non-probabilistic sampling for convenience, it was made up of 33 administrative auditors from 02 IAFAS of the private sector of Central Lima, to whom the questionnaire on the variables of financial education and personal finance management was applied. The results indicated that there is a significant correlation between the study variables, demonstrating that the administrative auditors of the IAFAS of Central Lima present a deficiency in financial knowledge, which is reflected in uninformed decisión-making or without advice. Therefore, the research concludes that financial education affects the management of the personal finances of the IAFAS administrative auditor; This is because it is important to have a basic understanding of financial concepts so that people do not find it difficult to properly manage their personal finances make their savings profitable and be able to make informed decisions, avoiding the increase of financial doubts.